227k views
2 votes
Solve the following exponential equations.
(10^x)^2 − 3(10^x) + 2 = 0

User ADH
by
4.9k points

1 Answer

7 votes

Answer:


x=(log(2))/(log(10))

Explanation:

Let:


y=10^(x)

So, rewritting the equation:


y^(2) -3y+2=0

Factoring:


(y-2)(y-1)=0

Therefore:


y=2\hspace{5}or\hspace{5}y=1

Substitute back for
y=10^(x)

for y=2

Taking the logarithm base 10 of both sides:


x=(log(2))/(log(10))

for y=1

Taking the logarithm base 10 of both sides and adding 1 to both sides:


log(1)+x=(log(2))/(log(10))


log(1)=0

so:


x=(log(2))/(log(10))

Hence:


x=(log(2))/(log(10))

User Kientux
by
4.8k points